Sometimes, winners lose: Economic disparity and indigenization in Kazakhstan - Ira N. Gang; Achim Schmillen (Rutgers University, Department of Economics, 2014)
Several post-Soviet states have introduced policies to improve the relative economic, political or social position of formerly disadvantaged populations. Using one example of such policies - "Kazakhisation" in Kazakhstan - we investigate their impact on the comparative earnings of two directly affected groups, ethnic Russians and ethnic Kazakhs. Oaxaca decompositions show that Kazakhs are better endowed with income generating characteristics but receive lower returns to these characteristics than Russians. The second effect dominates and Kazakhs have comparatively lower average living standards. While "Kazakhisation" may have been successful in a narrow sense - i.e., by empowering Kazakhs to take on leading positions in the public sector - more broadly it has been a self-defeating policy as it has pushed ethnic Russians into jobs that often evolved into positions that (at least in monetary terms) are superior now to those held by Kazakhs.
Keywords: I32; O12; J15; 330; ethnicity; decomposition; indigenization; Kazakhstan